ICG-loaded and 125I-labeled theranostic nanosystem for multimodality imaging-navigated phototherapy of breast cancer. (28th November 2022) - Wang, Dianyu; Yue, Jianlan; Cao, Qiannan; Liu, Jinjian; Yang, Lijun; Shen, Wen; Zhang, Wenxue; Liu, Jianfeng
Abstract : ICG-loaded and 125 I-labeled theranostic nanosystem with high biocompatibility for FLI/SPECT-navigated PTT/PDT of breast cancer. Abstract : Multimodality imaging-navigated precise phototherapy has been well-established as a promising strategy for enhancing the diagnostic and therapeutic efficiency of cancer in preclinical trials. However, proper theranostic agents with adequate biosafety and biological efficacy as well as simple components and preparations are still in great demand to promote the clinical translation of this regimen. Here, we developed a multifunctional nanosystem based on the self-assembly of FDA-approved indocyanine green (ICG) and 125 I-labeled glycopeptides, which were composed of FDA-approved natural polysaccharide sodium alginate and endogenous tyrosine, for fluorescence imaging/single photon emission computed tomography (FLI/SPECT)-guided synergistic photothermal/photodynamic therapy (PTT/PDT) of breast cancer. The as-prepared ICG@ADY( 125 I) NPs possessed a stable nanostructure and radiolabel, an ICG-equivalent ROS and hyperthermia generation property, and a preferable photo/photothermal stability and biocompatibility, favoring its tumor homing, multimodality imaging, and phototherapy with high biosafety. Consequently, ICG@ADY( 125 I) NPs smoothly accumulated in tumors by virtue of their long blood circulation ( t 1/2 = 15.76 ± 1.34 h) and the EPR effect, thereby presenting highly sensitive FLI/SPECT images to realize cancer diagnosis. Guided by multimodality imaging, accurate PTT/PDT was performed using NIR laser irradiation, achieving a high tumor inhibition rate (81.8%) against 4T1 breast cancer models without appreciable side effects. Altogether, this theranostic nanosystem may have huge potential for the clinical diagnosis and treatment of breast cancer.